Spindle cell variant of medullary thyroid carcinoma: a clinicopathologic study of four cases - Yan Xia Wang; Shou Jing Yang (BMC, 2021)
Abstract Background Medullary thyroid carcinoma (MTC) is a malignant tumor derived from C cells. It accounts for about 10% of all thyroid malignancies. More than 14 histological variants have been described. Among them, spindle cell variant is extremely rare. Case presentation Here we describe 4 cases of spindle cell variant of MTC collected from 2012 to 2019. Ultrasound showed solid and hypoechoic nodules. Three patients underwent total thyroidectomy and regional lymph node dissection, and 1 patient underwent thyroid mass resection. Histologically, the tumors showed spindle shaped cells in bundles or interlaced arrangement, separated by hyalinised fibrous stroma that contained amyloid deposits. Immunohistochemistry showed that the tumor cells were positive for calcitonin, chromogranin A, synaptophysin, CD56, and TTF-1, but negative for other lineage-specific markers. Conclusions We report 4 rare cases of spindle cell variant of MTC. Due to its rarity and special morphology, the diagnosis of spindle cell variant MTC relies on its morphology and immunohistochemical markers to avoid misdiagnosis.